(untitled) (Our Nature, 2018)
A field trial was carried out to test performance of four locally available substrates (split bamboo, whole bamboo, banana midrib and plastic bottle) for periphyton enhancement in farmer’s ponds at Seri and Nandapur in Nawalparasi district for 7 months. Six carp species were stocked at 15000 fish/hectare and SIS at unrecorded densities. Carp was fed with rice bran and mustard oil cake at 1.5% BW while grass carp was fed with grass and banana leaves at 50% BW. There was no significant effect of substrates on growth and production of carp. Combined NFY was 19% higher in plastic bottle ponds than control ponds, while NFY of SIS was 50% higher in banana midrib ponds than control and other substrate ponds. FCR was significantly better (P<0.05) in split bamboo ponds than control ponds. Banana midrib decayed fast and was replaced 3-4 times during experimental period while plastic bottles performed better in terms of production and profit.